Current Practice In Management Of Acute Coronary Syndrome In Tertiary Iraqi Cardiac Centers - Mayali, Ahmed (Karbala Journal of Medicine, 2019)
Abstract:- Background:- There is continued debate as to whether a routine, early invasive strategy is superior to a conservative strategy for the management of acute coronary syndromes. Aim of the study :- To verify current practice in the setting of management of acute coronary syndromes in tertiary cardiac centers in Iraq. Patients and methods:- Four hundred (400) patients were included in this study from 1st of January 2012 to 1st of January 2013from two tertiary Iraqi cardiac centers . Results & discussion:- Mean age for all patients was54.6±9.9 year,. In group A there was 208 male patients(69.3%),92 female patients (30.6%),in group B there was 65 male patients (65%), 25 female patients(25%). Low score found in 166(41.6%), intermediate score in 221 (55.3%), high in 13 (3.3%),no patients with high score was found in group B ,mean TIMI score in group A was 1.61±0.5,in group B was 1.60±0.5 (P value NS) .In group A UA found in 249 (83%),STEMI in 23 (7.7%),NSTEMI in 28 (9.3%).In group B UA in 79 (79%),STEMI in16 (16%),NSTEMI in 5 (5%) (Pvalue0.02). Smoking is prevalent more in group A( 186 patients (62%) versus 43 patients (34%) in group B), while diabetes mellitus and family history of premature coronary artery were more prevalent in group B (Pvalue0.03). All patients in group A with low score were treated medically while in group B with low score treated invasively. Invasive approach was more in group B compared with group A in intermerdiate risk score. Normal coronaries were found in (3.3%) in group A versus (6.8%) in group B. Percutaneous coronary intervention was applied in (66.6%) in group A versus (50%)in group B, surgery used in (23.3%)in group A versus (28.3%)in group B, medical treatment in (10%) in group A versus (21.6%) in group B. There were no statistical difference between both groups regarding duration of admission to hospital and mortality. Conclusion:-Management of acute coronary syndromes was the same between tertiary cardiac centers and it is progressing significantly in our country.